Fish/flaxseed oil protect against nitric oxide-induced hepatotoxicity and cell death in the rat liver. (March 2016) - Khan, MW; Priyamvada, S; Khan, SA; Khan, S; Gangopadhyay, A; Yusufi, ANK
Sodium nitroprusside (SNP) is an antihypertensive drug with proven toxic effects attributed mainly to the production of nitric oxide (NO). Polyunsaturated fatty acids (PUFAs) are widely regarded as functional foods and have been shown to ameliorate the harmful effects of many toxicants. This study examined whether feeding of fish oil (FO)/flaxseed oil (FXO) would have any protective effect against SNP-induced hepatotoxicity and cell death. Male Wistar rats were fed either on normal diet or with 15% FO/FXO for 15 days, following which SNP (1.5 mg/kg body weight) was administered intraperitoneally for 7 days. Animals were killed after treatment, and livers were collected for further analysis. We observed that SNP significantly elevated tissue nitrite levels and lipid peroxidation (LPO) with concomitant perturbation in antioxidant defense systems accompanied with dysregulated glucose metabolism and pronounced cellular death. FO/FXO supplementation to SNP-treated rats caused reversal of tissue injury/cell death and markedly decreased LPO and improved antioxidant defense systems. FO/FXO appear to protect against SNP-induced hepatotoxicity by improving energy metabolism and antioxidant defense mechanism.